Successive mini-cuttings collection in Piptocarpha angustifolia mini-stumps: effects on maturation, adventitious root induction and root vigor - Carlos André Stuepp; Ivar Wendling; Henrique Soares Koehler; Katia Christina Zuffellato-Ribas (Acta Scientiarum. Agronomy, 2017)
The low percentage of seed germination and adventitious root induction in cuttings of Piptocarpha angustifolia has limited its silvicultural use. Thus, we studied the effect of tissue maturation on successive collections of mini-cuttings grown in a semi-hydroponic system. Likewise, we evaluated potential multiplication via the mini-cutting technique by assessing the survival and productivity of mini-stumps as well as the formation of adventitious roots and the root vigor. We made 32 sprout collections during two years in a clonal mini-garden. From these collections, mini-cutting experiments were installed throughout several seasons. Mini-cuttings of 8±1 cm long were prepared, planted in boxes with vermiculite and carbonized rice husk (1:1 v/v) and placed in a greenhouse. After 70 days, we evaluated the adventitious rooting percentage as well as the adventitious root and aerial vigor of the mini-cuttings. The appropriate survival of mini-stumps (68%) and the annual production of mini-cuttings per square meter (2,227) reflected the efficiency of the semi-hydroponic system for this species. The increasing rooting, multiplication rate and root vigor indicate no maturity in the course of the collection of mini-cuttings in P. angustifolia mini-stumps.